Penguatan Kapasitas BUMDes Desa Pandean Melalui Transformasi Model Bisnis Berbasis Inovasi Sosial dan Digitalisasi Pemasaran - Tetuko Rawidyo Putro; Lukman Hakim; Siti Aisyah Tri Rahayu; Ariyanto Adhi Nugroho; Riwi Sumantyo; Mulyanto; Muhammad Yusuf Indra Purnama; Johadi; Hery Sulistio Jati Nugroho Sriwiyanto; Muhammad Bagus Sistriatmaja (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
The Pandean Village-Owned Enterprise (BUMDes) in Rembang District, Rembang Regency, is facing business stagnation due to the lack of an adaptive business model and minimal use of digital technology in marketing. This community service activity aims to strengthen the capacity of BUMDes through two main interventions: (1) mentoring in the preparation of a social innovation-based Business Model Canvas (BMC), and (2) marketing digitalization training including the creation of business social media accounts and online product catalogs. The method used is Community Based Participatory Action (CBPA) with active involvement of BUMDes administrators and village youth. The results of the activity show an increase in the average knowledge score of participants from 44.2 to 79.6 (an increase of 80.1%), the creation of a business model blueprint document, two active digital marketing platforms, and a projected increase in turnover of 17.5% in the first three months of implementation. This activity contributes to the achievement of SDG No. 4 (Quality Education) through increasing digital literacy and entrepreneurship, as well as SDG No. 5 (Education). 17 (Partnership to Achieve Goals) through strengthening collaboration between universities, village governments, and communities.